2007
DOI: 10.1097/01.nne.0000264327.17921.b7
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Ability of Nursing Students to Perform a Spiritual Assessment

Abstract: According to the literature, a majority of nurses and nursing students report a lack of comfort and ability to perform a spiritual assessment. The researchers designed and implemented an intervention program to address the 4 barriers most frequently identified as obstacles to performing a spiritual assessment. They discuss this study and suggest teaching interventions to assist nursing students to assess and implement spiritual care. Researcher-developed tools are presented and can be made available for use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 28 publications
0
43
0
Order By: Relevance
“…Although Tiew et al (2013) suggest that an understanding of spirituality and spiritual care did not necessarily influence practice, Hoffert et al, (2007) and Giske and Cone (2012) discovered that spirituality education enabled students to be more knowledgeable and comfortable performing spiritual assessments. In addition, Taylor et al, (1999) and Graham (2008) found that Students with a strong sense of personal spirituality felt comfortable and confident providing spiritual care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Tiew et al (2013) suggest that an understanding of spirituality and spiritual care did not necessarily influence practice, Hoffert et al, (2007) and Giske and Cone (2012) discovered that spirituality education enabled students to be more knowledgeable and comfortable performing spiritual assessments. In addition, Taylor et al, (1999) and Graham (2008) found that Students with a strong sense of personal spirituality felt comfortable and confident providing spiritual care.…”
Section: Discussionmentioning
confidence: 99%
“…Conclusions drawn from Hoffert et al (2007) are that spirituality is complex and perhaps intimidating, therefore, specific education and experience is required to build students' competence and confidence, a view supported by Greenstreet (1999) and Narayanasamy (1999). Furthermore, Baldacchino (2008a) suggests, a combination of knowledge and skills from a targeted course would embolden competence to deliver spiritual care.…”
Section: Spiritual Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In a review of papers on perceptions toward spirituality and spiritual care published from 2000 to 2012, 138 articles were identified, but only nine studies involved preregistration nursing students. A critical examination of these studies identified descriptions of spirituality content in curricula [6,16,20] and the impact of specific spiritual education modules or teaching strategies on students' spiritual perspectives [5]. In a review of the literature by Lewinson et al, it was reported that nurses were aware of their lack of knowledge, understanding and skills in the area of spirituality and spiritual care, and desired to be better informed and skilled in this area.…”
Section: Introductionmentioning
confidence: 99%
“…It has been emphasized in studies in this country and abroad that a lack of education is an important factor among the reasons for nurses not meeting the spiritual needs of individuals [5,8,16,17]. Also, McSherry reported that the concept of spirituality and spiritual care in nursing remained theoretical in the fields of organization, management and practice, and that going beyond this is necessary [18].…”
Section: Introductionmentioning
confidence: 99%